PROGRAM KESEJAHTERAAN SOSIAL DALAM PENANGGULANGAN GELANDANGAN PENGEMIS DI KOTA SERANG BANTEN - Siti Nurul Hamidah (Department of Islamic Community Development, Faculty of Da'wah, State Islamic University (UIN) of Sultan Maulana Hasanuddin Banten, 2019)
Tramp panhandler (Gelandangan Pengemis, called: Gepeng) is a social phenomenon that is a problem for every region in Indonesia. Gepeng is a promising job for some communities. Gepeng in Serang itself varies, from which can still suffice the need to be said to be sufficient and not including the poor households (RTM), to the poor who really belong to poor households (RTM). This article aims to analyze the background of the emergence of sprawl in Serang city. This paper uses the research method of the library study, discussing the sprawl in the city of Serang to provide the correct problem solving the mitigation in the city of Serang in an effort to realize social welfare. From the results of the study obtained data that the cause factor of the person chose to be a sprawl; Physical disabilities, age, education, economics, environment and religion.